Analisis Pengaruh Tingkat Pendidikan, Kesehatan dan Jenis Kelamin Terhadap TPAK di Sumatera Barat - Fuada, Nurul; Amar, Syamsul (Universitas Negeri Padang, 2023)
This study aims to determine and analyze the effect of Education Level, Health Level and Gender on the Labor Force Participation Rate in West Sumatra. This research uses panel data from 2017 to 2021 in 19 regencies/cities in West Sumatra which are sourced from the Central Bureau of Statistics. Before using the regression, the Chow test and Hausman test were carried out and the results of the analysis showed that the selected model was the Random Effect Model (REM)). The results of the study reveal that: (1) Education Level has a significant effect on the Labor Force Participation Rate in West Sumatra (2) Health Level has no significant effect on the Labor Force Participation Rate in West Sumatra (3) Gender has a significant effect on the Labor Force Participation Rate in West Sumatra . These findings confirm the role of the labor force participation rate in increasing the effectiveness of economic development. Based on the results of this study, it is suggested to the Government that it is necessary to increase the ease of access to education for the community. So that in the future there will be an increase in labor force participation in West Sumatra. labor force participation in West Sumatra.